2015
DOI: 10.1371/journal.pone.0140616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypoxic Interval Training and Hyperoxic Recovery on Muscle Activation and Oxygenation in Connection with Double-Poling Exercise

Abstract: Here, we evaluated the influence of breathing oxygen at different partial pressures during recovery from exercise on performance at sea-level and a simulated altitude of 1800 m, as reflected in activation of different upper body muscles, and oxygenation of the m. triceps brachii. Ten well-trained, male endurance athletes (25.3±4.1 yrs; 179.2±4.5 cm; 74.2±3.4 kg) performed four test trials, each involving three 3-min sessions on a double-poling ergometer with 3-min intervals of recovery. One trial was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…Accordingly, some studies have suggested that during exercise performed under local hypoxia the aerobic metabolism is decreased, while the anaerobic metabolism (i.e., alactic and lactic energy systems) is increased [ 9 , 10 ]. It is believed that increased anaerobic energy production may evoke higher metaboreflex activity and, consequently enhance heart rate (HR) response, cardiac output, and ventilation ( ) to adequately supply O 2 to exercising muscle and remove the metabolites generated from the anaerobic metabolism [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, some studies have suggested that during exercise performed under local hypoxia the aerobic metabolism is decreased, while the anaerobic metabolism (i.e., alactic and lactic energy systems) is increased [ 9 , 10 ]. It is believed that increased anaerobic energy production may evoke higher metaboreflex activity and, consequently enhance heart rate (HR) response, cardiac output, and ventilation ( ) to adequately supply O 2 to exercising muscle and remove the metabolites generated from the anaerobic metabolism [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although older studies showed that hyperoxia improves local muscle blood flow (at least in dogs) (Barclay et al., ), a recent investigation concluded that the less pronounced decline in mean power during three 3‐min double‐poling sprints under normoxic or hypoxic conditions with hyperoxic recovery was not related to alterations in muscle activity or oxygenation (Zinner et al., ). In fact, breathing 100% oxygen during a 4‐min recovery period between two bouts of exercise did not change the recovery of minute ventilation or heart rate or subsequent performance (Robbins et al., ).…”
Section: How Can Acute Hyperoxia Improve Human Performance?mentioning
confidence: 99%
“…Findings concerning the effects of hyperoxic breathing during recovery from high‐intensity exercise on subsequent performance and physiological responses remain inconclusive. Although hyperoxia promotes arterial O 2 saturation (Nummela et al., ), lessens perceived exertion (Peeling & Andersson, ), and is thought to allow more rapid recovery of phosphocreatine (Stellingwerff et al., ), hyperoxia during recovery from repeated intervals of high‐intensity exercise, including 3 × 3‐min sprints at ~1800‐m altitude (Hauser et al., ) or sea‐level (Zinner et al., ), as well as 5 × 30 s cycling sprints (Sperlich et al., ), did not improve performance. However, breathing pure oxygen during the 6‐min recovery period between 5 × 40 arm strokes on a swim bench improved the peak and mean power outputs during the third, fourth, and fifth intervals (Sperlich et al., ).…”
Section: How Can Acute Hyperoxia Improve Human Performance?mentioning
confidence: 99%
“…В развернутых ответах авторы [73] приводят результаты исследований, которые подтверждают, что: а) данные о влиянии гипероксии при восстановлении после высокоинтенсивного упражнения на последующую работоспособность неубедительны [35,57,72,82]; б) даже если имеются изменения в физиологических показателях в результате тренировок в условиях гипероксии, показатели изученной ферментной активности мышц, определяющих работоспособность, не отличаются от таковых при нормоксии, а работоспособность спортсменов не увеличивается [43,59]; в) гипероксия, содействуя артериальной сатурации O 2 [52], уменьшает ощущение возбуждения в интервалах восстановления между повторяющимися высокоинтенсивными и спринтерскими упражнениями как в условиях среднегорья, так и на уровне моря, не улучшает работоспособность [35,72,86].…”
Section: Keywordunclassified